Retail event satisfaction measurement model: an Indian context. (21st July 2009) - Hemalatha, M.; Sivakumar, V.J.
This study made an attempt to identify the dimensions of retail event satisfaction based on the retail strategy mix which influences the shopper's shopping behaviour. First, we developed a scale for measuring the retail event retail mix by literature review and focus group interview. Then, we checked the reliability and validity of the instrument developed. Finally, we developed a model for the retail event satisfaction measurement which will help the retailers to decide their retail strategy mix for planning retail events. The model has been built based on the factors which influences the shopping behaviour of apparel shoppers during the Aadi sale, a retail event celebrated in the southern part of India. The result of multiple regression analysis of the retail event depicts that merchandise, customer service and discount are the most important retail mix for the shoppers during the Aadi sale retail event.